DAYA TARIK PESAN NILAI BUDAYA PADA FILM ANIMASI RAYA AND THE LAST DRAGON - Ade Rachmawati (Management of Education: Jurnal Manajemen Pendidikan Islam, 2023)
This study aims to analyze the cultural values and appeal of Disney's animated film "Raya and the Last Dragon". This study uses a qualitative approach to explore the meaning, messages, and cultural representations in the film. Research data was collected through content analysis, observation, and interviews with viewers who had watched this film. The results of the research are expected to provide insight into how animated films are able to convey cultural values and what factors make this film attractive to audiences.